2022
DOI: 10.11152/mu-3263
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of lung ultrasound in the early identification of severe COVID-19: results from a prospective study

Abstract: Aim: There is growing evidence regarding the imaging findings of coronavirus disease 2019 (COVID-19) in lung ultrasound (LUS); however, its role in predicting the prognosis has yet to be explored. The aim of the study was to assess the relationship between lung ultrasound findings with the degree of respiratory failure measured by the PaO2/FiO2 ratio (PaFi) andthe prognosis of these patients: need for non-invasive mechanical ventilation (NIMV), admission to the Intensive Care Unit (ICU) and mortality.Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
5
0
3
Order By: Relevance
“…Berce et al underline the importance of LUS as a useful method in a bacterial or viral outbreak or in epidemic times [ 30 ]. Lately, several studies have shown a significant role of LUS in the evaluation of COVID-19 pneumonia, not only regarding its accuracy in the detection of lesions, but also in evaluating the risk of death and complications development [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berce et al underline the importance of LUS as a useful method in a bacterial or viral outbreak or in epidemic times [ 30 ]. Lately, several studies have shown a significant role of LUS in the evaluation of COVID-19 pneumonia, not only regarding its accuracy in the detection of lesions, but also in evaluating the risk of death and complications development [ 8 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an added value, especially if we take into account the AUCs reached ( Table 2 and Supplementary Table S2 ). Most of the predictive models in which clinical variables [ 9 ] or lung ultrasound [ 37 , 38 ] are used only contemplate mortality as the primary outcome, when identifying those patients who require early intubation is probably more practical to improve care, and this fact makes our models more attractive.…”
Section: Discussionmentioning
confidence: 99%
“…4. Ausencia de enfermedad crítica en el momento de la inclusión [10][11][12][13][14][15][16] en el estudio según la clasificación de la Guía de COVID-19 del NIH 14 . 5.…”
Section: Enfermedad Leve Moderada O Grave Según La Clasificación De Launclassified
“…La exploración ecográfica pulmonar se realizó siguiendo el protocolo Hernández-Píriz et al 15 . Se exploraron 13 áreas (3 en región posterior y 2 en cara lateral de ambos pulmones, 2 en cara anterior de pulmón derecho y 1 en cara antero-superior de pulmón izquierdo).…”
Section: Exploración Ecográficaunclassified
See 1 more Smart Citation